Trabalhadores em contrato intermitente no Brasil: Evoluç\~ao, cenários e perfil dos contratados pós-reforma trabalhista de 2017 - Alanna Santos de Oliveira; Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Among the institutional transformations proposed by the Labor Reform approved in 2017, the proposal of a new type of contract, called "intermittent", stands out. Although this modality does not constitute an innovation, its adoption is undeniable and, more specifically in Brazil, its dissemination in an economy with problematic structural aspects in the construction market deserves careful analysis. Therefore, this paper seeks to promote an analysis of the evolution of intermittent job evolution in the country, combined with a delineation of a profile of its workers, employing descriptive statistics, as well as logit regression, besides making projections to evaluate the possible effects of a spread of this type of contract. The results show that, although the intermittence still has a modest participation in the conformation of the Brazilian formal employment stock, it is possible to observe an increasing number of admissions within the net annual movements; and conjectures suggest that the growing importance of intermittent work could lead to not negligible changes in the sectoral structure of employment, such as the reinforcement of exclusionary stigmas, a reduction in the wage bill and an increase in income inequality. Besides that, logit results show that younger people, non-white color and without higher education constitute the most likely to intermittent employment.
Keywords: J08; 330; labor reform; intermittent contract; job market; inequality; social security protection